THE ROLE OF INTERCULTURAL COMMUNICATION COMPETENCE IN FOREIGN LANGUAGE TEACHING: CHALLENGES AND OPPORTUNITIES IN UZBEKISTAN - Muxtarov Abduvali,; To`raxon Abdurahmonov, (TADQIQOTLAR, 2026)
Introduction In  today’s  globalized  world,  the  ability  to  communicate  effectively  across cultural boundaries has become an essential skill. Foreign language education is no longer limited to mastering grammar and vocabulary; it increasingly encompasses the development  of  intercultural  communication  competence  (ICC).  ICC  refers  to  the ability to interact appropriately and effectively with individuals from diverse cultural backgrounds. This competence enables language learners to navigate cultural nuances, avoid  misunderstandings,  and  engage  in  meaningful  communication  in  real-life contexts. The  Republic  of  Uzbekistan,  amid  its  rapid  integration  into  the  global community,  has  recognized  the  importance  of  ICC  in  foreign  language  teaching. Recent curriculum reforms emphasize national and global cultural competencies as critical  outcomes  for  students.  However,  challenges  remain  in  teacher  training, curriculum design, and resource availability, which hinder the full integration of ICC into language education. This thesis explores the role of intercultural communication competence in foreign language teaching, examines current pedagogical approaches, and discusses the practical challenges and opportunities related to its implementation in Uzbekistan’s educational context.